Contrasting Air Mass Advection Explains Significant Differences in Boundary Layer Depth Seasonal Cycles Under Onshore Versus Offshore Flows. Issue 5 (1st March 2019) - Pal, Sandip; Lee, Temple R.
Abstract: The complexities in the atmospheric boundary layer depth (BLD) features over coastal regions pose challenges for meteorological forecasts, air quality, greenhouse gas mixing and transport, and wind energy production. Here, for the first time, we investigated afternoon BLD variability over 18 coastal sites in the contiguous United States located along the Gulf of Mexico, Atlantic Ocean, and Pacific Ocean using 25 years of rawinsonde launches. Due to influence of shallow marine layer air via onshore flow, substantially large BLD contrasts (∆BLD, BLD under offshore minus onshore) were found. ∆BLDs over the sites varied both seasonally and spatially among the coastal regions and within a region. For the sites along the Gulf of Mexico and Atlantic Ocean, ∆BLDs were found to be higher in spring and summer (500–1, 500 m) than in winter and fall (100–450 m). Results underscore the importance of advection on BLD footprints and provide observational constraints for model evaluation. Plain Language Summary: The depth of the Earth's atmospheric boundary layer is an important parameter that atmospheric scientists use in weather forecast models and for understanding the height to which pollutants emitted from Earth's surface are mixed into the atmosphere. In our study, we investigated how the depth of the boundary layer varied at coastal sites along the Gulf of Mexico, Atlantic Ocean, and Pacific Ocean using 25 years of boundary layer depths obtained using weather balloon launches. We found large differences in boundary layer depths that depended on whether the wind was blowing onshore or offshore. Offshore winds resulted in much deeper boundary layers than onshore winds. The difference between boundary layer depths when the wind was offshore versus onshore was largest during the spring and summer at sites located along the Gulf of Mexico and Atlantic Ocean. Key Points: Using 25‐year rawinsonde observations, we report on the boundary layer depth variability over 18 coastal sites in the contiguous United States Striking differences emerged in the boundary layer depths due to interplay between marine air mass and continental air mass The offshore versus onshore contrasts in the boundary layer depths vary both seasonally and spatially among the coastal regions